FISHERMEN ALTERNATIVE JOBS ON THE KELURAHAN TELUK KABUNG SELATAN KECAMATAN BUNGUS TELUK KABUNG DISTRICT WEST SUMATERA BARAT - Ivalni Febria Ananda; Darwis Darwis; Firman Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRAK This research was conducted in July 2017 in Teluk Kabung Selatan Village, Bungus Teluk Kabung District, West Sumatera Province. This study was aimad to determine the types of alternative jobs undertaken fishermen nets, and income as fishermen and alternative jobs, and income contribution from alternative jobs to fishermen's income in Teluk Kabung Selatan Village. The method used in this study is a survey with the number of respondents as many as 35 people. The types of altrnative jobs done by fisherman in Teluk Kabung Selatan Village are farm laborers, sea transportation services, and water game rentals. The fisherman income from alternative employment averaged IDR.631,142 / month while income from basic work as fisherman averaged IDR.817.142 / month. Revenue contribution from alternative household employment is monthly average 44,18% to household income of fishermen. Keywords:Alternative jobs, Contribution, Fisherman Nets,Teluk Kabung Selatan